Accelerating progress towards biodiversity targets through agroecology - Jones, Sarah; Declerck, Fabrice; Elias, Marlene; Estrada Carmona, Natalia; Geck, Matthias; Kettle, Christopher; Masso, Cargele (2024)
Food and biodiversity challenges are deeply interconnected, requiring systems approaches that address these and other interconnected socio-ecological challenges simultaneously. Systems approaches recognize synergies and trade-offs across multiple objectives and stakeholders and focus on finding solutions that enable progress in multiple areas. Agroecology forms part of this solution space, encompassing interventions at field, farm, landscape and food system level that build ecological resilience, deliver nutritious diets, and lead to economically prosperous and fairer societies. Agroecology is embodied in Target 10 of the Kunming-Montreal Global Biodiversity Framework (GBF) yet contributes directly or indirectly to all of the GBF targets.